Georgian Mathematical Journal (Berlin ; Boston De Gruyter, 1994)
The Georgian Mathematical Journal was founded by the Georgian National Academy of Sciences and A. Razmadze Mathematical Institute, and is jointly produced with De Gruyter.The concern of this international journal is the publication of research articles of best scientific standard in pure and applied mathematics. Special emphasis is put on the presentation of results obtained by Georgian mathematicians.
Popis urobený na základe e-zdroja z webstránky vydavateľa (viewed 17. Aug 2020)
Obsahuje bibliografické odkazy.
textový dokument
Internet via World Wide Web.
Keywords: General Mathematics; Mathematik; General Mathematics; Mathematik; elektronické časopisy; časopisy